2019
DOI: 10.1038/s41419-019-1728-5
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin alleviates the pyroptosis of Leydig cells by promoting autophagy via the ROS–AMPK–mTOR axis

Abstract: Adrenomedullin (ADM) exerts anti-oxidant, anti-inflammatory and anti-apoptotic effects in Leydig cells. However, the role and mechanism of ADM in the pyroptosis of Leydig cells are poorly understood. This study first showed the protective effects of ADM on the pyroptosis and biological functions of Leydig cells exposed to lipopolysaccharide (LPS) by promoting autophagy. Primary rat Leydig cells were treated with various concentrations of LPS and ADM, together with or without N-acetyl-L-cysteine (NAC) or 3-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
139
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(149 citation statements)
references
References 43 publications
10
139
0
Order By: Relevance
“…Among them, pyroptosis has recently been discovered as a pro-inflammatory programmed cell death process that plays an important role in cerebral I/R injury (Xia et al, 2018 ; Zhu et al, 2019 ). Recent studies have suggested that activation of autophagy has a potential therapeutic effect on cerebral I/R injury (Yao et al, 2019 ), and the mechanism of autophagy may be related to the inhibition of pyroptosis in some tissue injury (Li et al, 2019 ), which still remains unclear in cerebral I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, pyroptosis has recently been discovered as a pro-inflammatory programmed cell death process that plays an important role in cerebral I/R injury (Xia et al, 2018 ; Zhu et al, 2019 ). Recent studies have suggested that activation of autophagy has a potential therapeutic effect on cerebral I/R injury (Yao et al, 2019 ), and the mechanism of autophagy may be related to the inhibition of pyroptosis in some tissue injury (Li et al, 2019 ), which still remains unclear in cerebral I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Adrenomedullin restored the steroidogenic enzyme expression, including StAR, CYP11A1, 3β-HSD, and CYP17A1, and testosterone production in LPS-induced Leydig cells via activation of the mTOR signaling pathway (Li et al, 2019). Nicotine decreased testosterone synthesis via inhibition of the mTOR signaling pathway in Leydig cells .…”
Section: Discussionmentioning
confidence: 85%
“…The mTOR signaling pathway was involved in the upregulation of the release of both progesterone and testosterone in porcine granulosa cells (Sirotkin et al, 2015). Adrenomedullin restored the steroidogenic enzyme expression, including StAR, CYP11A1, 3β‐HSD, and CYP17A1, and testosterone production in LPS‐induced Leydig cells via activation of the mTOR signaling pathway (Li et al, 2019). Nicotine decreased testosterone synthesis via inhibition of the mTOR signaling pathway in Leydig cells (Zhao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Q10 reduced the level of ROS to protect astrocytes from oxidative stress (Jing et al 2015). ROS induced autophagy that was associated with the ROS-AMPK-mTOR pathway (Li et al 2019;Yang et al 2019).…”
Section: Discussionmentioning
confidence: 99%